Successful use of pessary for uterine prolapse after pelvic trauma in a nulliparous young female: A case report. Issue 12 (March 2018) - Ai, Fang-Fang; Mao, Meng; Zhang, Ye; Kang, Jia; Zhu, Lan
Abstract: Rationale: To date, sporadic studies have shown that a relationship exists between delayed pelvic organ prolapse (POP) and pelvic trauma, and these cases have all been managed with surgical procedures. Patient concerns: A 29-year-old, nulliparous (Gravida 0) woman without sexual experience was referred to our gynecology outpatient clinic, complaining of a protruding vaginal mass 5 years after a traffic accident (hit by a truck when she was walking) that caused serious multiple injuries. Diagnoses: Stage 2 cystocele, stage 3 uterine prolapse, and stage 2 rectocele, pelvic trauma history. Interventions: The woman was successfully managed with the Gellhorn size 2 pessary use. Outcomes: The short-term effect of pessary use was significant improvement. Lessons: This is the first case report of the successful use of a pessary for POP after pelvic trauma in a nulliparous young female.